2021
DOI: 10.3390/jcm10153318
|View full text |Cite
|
Sign up to set email alerts
|

Association between Subclinical Hypothyroidism and Incident Hypertension in Women: A Systematic Review and Meta-Analysis

Abstract: Subclinical hypothyroidism (SCH) has been found to be associated with an increased risk of cardiovascular diseases. However, there is no clear consensus on the relationship between SCH and hypertension (HTN). We sought to investigate the association between SCH and incident HTN in women. MEDLINE and EMBASE databases were searched for studies that reported the incidence of HTN in females with SCH versus without SCH. Pooled odds ratio (OR) and 95% confidence interval (CI) of the outcome were obtained using a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…Positive cross-sectional associations were reported for indices of pituitary sensitivity to thyroid hormones with BP, but the analysis by Yang et al was not stratified by sex ( 33 ). In addition, some studies have shown associations of hypothyroidism with DBP ( 68-71 ), particularly in women ( 72 ), while hyperthyroidism was associated with SBP ( 27 ). The present study could not examine associations of thyroid-related hormones with isolated systolic and diastolic hypertension because of the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Positive cross-sectional associations were reported for indices of pituitary sensitivity to thyroid hormones with BP, but the analysis by Yang et al was not stratified by sex ( 33 ). In addition, some studies have shown associations of hypothyroidism with DBP ( 68-71 ), particularly in women ( 72 ), while hyperthyroidism was associated with SBP ( 27 ). The present study could not examine associations of thyroid-related hormones with isolated systolic and diastolic hypertension because of the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto a la tensión arterial y los efectos cardiovasculares, encontramos en nuestro estudio, por medio del valor de Fisher, un riesgo aumentado de presentar mayores complicaciones con respecto a la media estudiada en otro protocolo realizado por el national health and nutrition examination survey; se estudiaron mediante análisis de percentiles, para estimar los riesgos, encontrándose aumento en todas las causas asociadas a hipotiroidismo IC95%, coincidiendo con los resultado obtenidos (23). En cuanto a las cifras de tensión arterial aumentada con respecto a la media de los pacientes con diagnóstico único de hipotiroidismo subclínico sobre los que coexisten con síndrome metabólico, se encuentra que existe una asociación positiva de la aparición de hipertensión arterial en los pacientes, esto contrastándolo con un metaanálisis realizado en 2021, IC 95% (24). Un factor importante encontrado que no se excluye en nuestro protocolo fue la relación de síndrome de ovario poliquístico e hipotiroidismo subclínico en la mujer.…”
Section: Discussionunclassified
“…However, only LDL reached a pathological level. The association between hypothyroidism and dyslipidemia is widely studied in literature [25][26][27]. A newly published meta-analysis showed a signi cant association between hypothyroidism and altered lipid pro le in the adult population [28].…”
Section: Discussionmentioning
confidence: 99%